THE IMPACT OF CORRUPTION, INFLATION AND UNEMPLOYMENT TOWARDS POVERTY IN INDONESIA - Muhammad Rizki; Keisha Dinya Solihati (Journal of Business Administration Economics & Entrepreneurship, 2022)
Poverty is one of the main problems regarding economic aspects in countries around the world including Indonesia. This research aims to analyze the correlation between the level of corruption perception index, inflation rate and unemployment rate towards poverty rate in Indonesia with the time span from 1998 – 2017. Data used on this research is from secondary data. Corruption perception index data is collected from Transparency International, hence inflation rate, unemployment rate and poverty rate are collected from Central Bureau of Statistics Indonesia. The data analysis technique in this research is using multiple regression analysis. Based on the research result, it shows that corruption, inflation and unemployment altogether are creating a significant effect on poverty. The result also shows that both corruption and inflation bring significant effect on poverty, while unemployment alone has no significant effect on poverty. The research result is expected to be a reference for the government of Indonesia and other countries in overcoming poverty problem.Keywords: Corruption, Inflation, Unemployment, Poverty